Strengthening Local Values of Arabica Coffee Farming in the Rural Area of Mount Latimojong, South Sulawesi - Haslinda, Haslinda; Irmayani, Irmayani; Ambar, Abdul Azis; Putera, Muh. Ikbal (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research aims to analyze the role and reinforcement of local values, particularly the practice of kombong or mutual cooperation, in supporting the sustainability of Arabica coffee farming in the rural area of Gunung Latimojong, Enrekang Regency, South Sulawesi. With a descriptive qualitative approach, data were collected through in-depth interviews and focus group discussions (FGDs) involving coffee farmers, community leaders, local government, and academics. The research results show that kombong plays an important role in maintaining social, economic, and ecological sustainability, as well as supporting operational efficiency through communal land management that does not rely on modern agricultural tools. However, modernization and the shift in interest of the younger generation towards other sectors are beginning to threaten the sustainability of these practices. These findings emphasize that the sustainability of coffee farming does not only depend on ecological and economic practices but also on the regeneration of local cultural values through the integration of relevant innovations to rekindle the interest of the younger generation. This conclusion expands the literature on sustainability based on local values and recommends cross-sectoral collaboration between the government, academics, and local communities to ensure that agriculture systems based on local wisdom remain adaptive amidst the challenges of modernization.